2007
DOI: 10.1562/0031-8655(2000)0720135uiegfr2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

UVB-induced Epidermal Growth Factor Receptor Phosphorylation is Critical for Downstream Signaling and Keratinocyte Survival ¶

Abstract: We have recently shown that UVB radiation activates epidermal growth factor receptor (EGFR)/extracellular regulated kinase 1 and 2 (ERK1/2) and p38 signaling pathways in keratinocytes. However, the functional relevance of these processes for downstream signaling and cell survival remains to be determined. The specific EGFR inhibitor PD153035 markedly decreased UVB‐induced phosphorylation of EGFR, ERK1/2 and shc, whereas p38 activation was unaffected. PD153035 pretreatment followed by UVB reduced clonogenic pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Peus et al (1999bPeus et al ( , 2000 have demonstrated that ERK, JNK, and p38 are activated in human epidermal keratinocytes following exposure to UVB irradiation. Several lines of evidence have supported that the activation of these kinases correlates with skin cell death in response to UVB (Assefa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Peus et al (1999bPeus et al ( , 2000 have demonstrated that ERK, JNK, and p38 are activated in human epidermal keratinocytes following exposure to UVB irradiation. Several lines of evidence have supported that the activation of these kinases correlates with skin cell death in response to UVB (Assefa et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of an EGFR-PI3K-AKT pathway is essential for the anti-apoptotic response of keratinocytes in response to ultraviolet B (UVB) radiation (FIGURE 5) (430). UV light inhibits the phosphatase activity, leading to activation of RTKs like EGFR (268).…”
Section: A Egfr Activation and Skin Homeostasismentioning
confidence: 99%
“…Epidermal growth factor (EGF) receptor, 12-O-tetradecanoyl-phorbol-13-acetate (TPA), and tumor necrosis factor-a have been used to study UVB-mediated promotional events in JB6 cells (7,18). Inhibition of EGF pathway affords resistance to UVB-mediated cell transformation (7).…”
Section: Introductionmentioning
confidence: 99%